STRATEGI COPING STRESS TENAGA KESEHATAN NUSALAUT - Debora Victori I Hetharia (Fakultas Kedokteran Universitas Pattimura, 2023)
Nusalaut is a sub-district located in Central Maluku Regency. Nusalaut, from a health perspective, has 1 health center which is classified as a very remote health center according to the 2020 Central Maluku Regency regent's regulation. Many problems contribute to stressors for health workers in carrying out work assignments in Nusalaut. The application of an adaptive stress coping mechanism is expected to help health workers in island areas such as Nusalaut, with all the difficulties and demands they face, be able to carry out their duties properly so that stress events do not affect the performance of health worker services. The purpose of this study was to find out the strategy of health workers in coping with stress, especially for health workers who work in Nusalaut District, Central Maluku Regency. The research method used is descriptive qualitative, with a field research design and research methods in the form of observation, interviews, and documentation. The results showed that 4 of the 7 health workers who were the sample used stress coping strategies that focused on Emotional Focused Coping and the remaining 3 used Problem Focused Coping. Then from the 7 community leaders in each country (village), each figure admitted that the community was satisfied with the services provided by the health workers, but for the countries of Nalahia and Sila-Leinitu, there were complaints. Each stress coping strategy used by each health worker should not reduce performance and become an obstacle in providing health services.